Effect of Feeding Bawang Dayak (Eleutherine palmifolia) Meal in A Diet Containing Lemuru Fish Oil on the Performance and Egg Quality of Japanese Quail - Haerul, Muhammad; Hermana, Widya; Sumiati (Faculty of Animal Science, Universitas Brawijaya, 2024)
This study evaluated the effects of feeding bawang dayak (Eleutherine palmifolia) meal ina diet containing Lemuru fish oil on performance and on egg quality in quails. This study used a layerof 160 quail with a Coturnix-Coturnix japonica strain aged 8 weeks. A completely randomized design (CRD) with four treatments, four replications and ten quail per replication was used in this experiment. The treatments consisted of R1 = basal diet without bawang dayak meal (control diet), R2 = basal diet containing 0.1% bawang dayak meal, R3 = basal diet containing 0.2% bawang dayak meal, and R4 = basal diet containing 0.3% bawang dayak meal. The variables observed were quail performance, egg physical quality, and cholesterol egg yolk level. The data were analysed using analysis of variance (ANOVA) and the post hoc Tukey test. The results showed that the use of bawangdayak meal had no significant effect (p>0.05) on quail performance or egg physical quality but had a significant effect (p<0.05) on cholesterol in the egg yolk. In conclusion, feeding bawang dayak meal up to 0.3% in a diet containing lemuru fish oil did not negatively impact quail productivity and can increase feed efficiency. Feeding 0.3% bawang dayak meal can reduce cholesterol in egg yolks.